Repellent effect of topical deltamethrin on blood feeding by Culicoides on horses. (30th May 2015) - Robin, M.; Archer, D.; McGowan, C.; Garros, C.; Gardès, L.; Baylis, M.
Abstract : African horse sickness (AHS) is a vectorborne disease spread by Culicoides biting midges. The UK's Department for Environment, Food and Rural Affairs currently suggests using topical deltamethrin for AHS control; however, no data are available regarding its efficacy in the horse. The aims of this study were to investigate the effect of topical deltamethrin on blood feeding by Culicoides on horses and to investigate which Culicoides species blood fed on horses. Three pairs of horses were placed in partially enclosed cages that allowed samples representing the Culicoides interacting with individual horses to be sampled. Four data collection sessions were completed before one horse from each pair was topically treated with 10 ml of 1 per cent deltamethrin solution and another four sessions were then carried out. Collected Culicoides were identified and each biting midge examined to see if it had blood fed. The most abundant species collected were C. chiopterus, C. dewulfi, C. obsoletus and C. scoticus (44.3 per cent) and either C. pulicaris or C. punctatus (34.7 per cent). These species were also more likely to have blood fed than other species, supporting their potential role as AHS vectors if the virus were to reach the UK. There was no significant effect of treatment on blood feeding by Culicoides . The results do not support the use of topical deltamethrin to prevent blood feeding by Culicoides on individual horses; however, the study does not investigate the effect that the widespread use of topical deltamethrin might have on vector numbers or disease transmission from viraemic individuals during an outbreak of AHS.